Germline and somatic genetic variability of oxysterol-related genes in breast cancer patients with early disease of the luminal subtype - Holý, Petr; Hlaváč, Viktor; Ostašov, Pavel; Brynychová, Veronika; Koževnikovová, Renata; Trnková, Markéta; Kopečková, Kateřina; Měšťáková, Soňa; Mrhalová, Marcela; Souček, Pavel (Biochimie, 2022)
Oxysterols, oxidized derivatives of cholesterol, have been implicated in multiple pathologies, including cancer. In breast cancer, the link is especially strong due to interactions between oxysterols and estrogen receptor activity. Here, we provide the first dedicated study of 113 oxysterol-related genes in breast cancer patients of the luminal subtype, in terms of both their somatic and germline variability, using targeted high-throughput DNA sequencing of 100 normal-tumor pairs with very high coverage. In the full cohort, or subsets of patients stratified by therapy, we found 12 germline variants in ABCA1, ABCA8, ABCC1, GPR183, LDLR, MBTPS1, NR1I2, OSBPL2, OSBPL3, and OSBPL5 to associate with poor survival of patients and variants in ABCA8, ABCG2, and HSD3B7 (three in total) associated with better survival. However, no associations remained significant after correction for multiple tests. Analysis of somatic variants revealed significantly (after FDR correction) poorer survival in patients mutated in CYP46A1 and 9 interacting (according to STRING analysis) genes, as well as in OSBPL3 and a set of 20 genes that collectively associated with the progesterone receptor status of patients. We propose further exploration of these genes in an integrative manner together with gene expression and epigenomic data.
Keywords: Prognosis; Receptors, Steroid; nádory prsu; Variant; lidé; Humans; Mutation; Germ Cells; Breast cancer; Oxysterols; kohortové studie; zárodečné buňky; oxysteroly; Genomics; steroidní receptory; High-Throughput Nucleotide Sequencing; Cohort Studies; ženské pohlaví; Female; Breast Neoplasms; vysoce účinné nukleotidové sekvenování